Nörolojik Hastalıklarda Balneoterapi - Akyıldız Tezcan, Ezgi (Geçmişten Günümüze Rehabilitasyonda Balneoterapi ve Hidroterapi, 2024)
Balneoterapi, tarihsel kullanımı binlerce yıl öncesine uzanan kadim bir yöntemdir. Geleneksel olarak cilt hastalıkları ve kas-iskelet sistemi bozuklukları gibi çok çeşitli rahatsızlıkların tedavisinde kullanılır. Bu bölümde ele alınan konu ise nisbi olarak daha az araştırılan bir yönü olan nörolojik hastalıklarda balneoterapinin kullanımıdır. Balneoterapi termal, mekanik ve kimyasal özelliklerinden kaynaklanan geniş bir terapötik etki yelpazesi sunabilmektedir. Bu etkileri kas gevşemesi, dolaşımın iyileştirilmesi, ağrının azaltılması ve psikolojik rahatlama gibi çeşitli yollarla sağladığı düşünülmektedir. Birçok nörolojik hastalıkta kişilerin semptom ve bulgularına göre balneoterapi uygulanabilmektedir. Özellikle Parkinson hastalığında yaşam kalitesi artışı, psikolojik iyi olma algısı, yürüyüş ve dengenin iyileştirilmesi; serebral palsili hastalarda günlük yaşam özerkliğinde ve yaşam kalitesinde artış; inme sonrası hastalarda spasitede ve ağrıda azalma etkileri öne çıkmaktadır. Ancak bu konuda bilimsel kanıtlar halen yetersizdir. Kişiselleştirilmiş tedavi protokollerinin geliştirilmesi, bütünsel tedavi yaklaşımlarının entegrasyonu ve balneoterapinin moleküler mekanizmalarının daha iyi anlaşılması gelecekteki araştırmalarda önem taşımaktadır.Balneotherapy, an ancient therapeutic method with historical roots extending thousands of years, has been traditionally employed to address a broad spectrum of conditions, including skin ailments and musculoskeletal disorders. This section delves into its application within the realm of neurological diseases—a facet that remains comparatively underexplored. Through its thermal, mechanical, and chemical properties, balneotherapy is posited to unleash a plethora of therapeutic effects. Balneotherapy is recognized for its multifaceted therapeutic impact, which encompasses promoting muscle relaxation, boosting blood flow, diminishing pain, and offering psychological comfort. These benefits are thought to be particularly adaptable to the diverse symptoms and clinical presentations observed in a range of neurological disorders. Notably, in the context of Parkinson's disease, balneotherapy has been associated with improved gait and balance, heightened perceptions of psychological well-being, and an overall enhancement in quality of life. For individuals with cerebral palsy, it contributes to increased autonomy in daily activities and elevates life quality. Additionally, its role in mitigating spasticity and pain has been particularly highlighted in post-stroke rehabilitation. Despite these promising avenues, the corpus of scientific evidence substantiating balneotherapy’s efficacy in neurological disorders remains limited.Future research endeavors must prioritize the formulation of personalized treatment protocols, the harmonization with holistic therapeutic strategies, and the elucidation of balneotherapy’s underlying molecular mechanisms. Such focused investigations are imperative to fully leverage balneotherapy’s potential in neurorehabilitation and to integrate this traditional therapy more firmly into contemporary medical practice.